RIESGO DE RECIDIVA LOCAL EN LA CIRUGÍA CONSERVADORA MAMARIA: EL PROBLEMA DE LOS MÁRGENES - Vuoto, Héctor D.; Candás, Gabriela B.; Uriburu, Juan Luis; Isetta, Juan A.M.; Cogorno, Lucas; Freijido, Ana S.; García, Alejandra M.; Bernabó, Oscar L. (Revista Argentina de Cirugía, 2022)
Introduction: Breast conserving surgery foIIowed by radiation therapy in earIy stage breast cancer are the stan- dard therapeutics at present. The incidence of IocaI recurrence (LR) varies between 4,1 and 18 %. Objective: To evaIuate the resection margins as LR risk factor foIIowing breast conserving treatment in patients undergoing surgery at the Breast Diseases Division of the British HospitaI and to anaIyze the impact on overaII survivaI. Material and Methods: 830 patients operated on between January 1988 and December 2005; 87 deveIoping recurrences after a median time of 71,9 months were anaIyzed retrospectiveIy. Results: The LR annuaI risk was 1,29 %. We observed LR in 15,7% in patients which resection margins were ≤ 5mm and 7,4% when resection margins were ≥ 6mm. The five year overaII survivaI rate in LR patients was 95,2%, at ten years 86,1% and at fifteen years 78,4%. Conclusions: Margins ≤ 5mm are an independent risk factor for IocaI recurrence. LR patients presented Iess sur- vivaI chances and higher risk of deveIoping distant metastasis.